Math microcapsules: an experience in the mathematics classes of the Colegio Científico Costarricense, Puntarenas - Parra Salazar, Edward (2022)
This article shows the experience of applying a learning resource based on microlearning as an alternative to build basic mathematical knowledge of students entering the Colegio Científico Costarricense of Puntarenas. In this paper, research based on design was used. At the same time, it was decided to promote informal learning as an element of complementarity in the mathematics class. The learning resource (microcapsules) encouraged the use of mobile devices to build knowledge about mathematical topics. Moreover, the use of design-based research enhanced the active role of the student and generated new fields to continue experimenting with microcapsules in other areas of scientific work.